Un gioco di parole nell’Apocolocyntosis - Berti, Emanuele (Lucius Annaeus Seneca, 2021)
Seneca’s use of participle morantibus in Apoc. 9.1 reveals a translinguistic wordplay between the Latin verb mǒror and the Greek adjective μωρός, which targets the proverbial stupidity of the recently deceased emperor Claudius and draws on a similar wordplay coined, according to Suetonius, by the new princeps Nero, his successor. Another allusion to the same wordplay is probably present also in the neologism fatuari (from fatuus, the Latin word corresponding to μωρός) in Apoc. 7.1. This net of allusions supports the hypothesis that Seneca composed his Apocolocyntosis primarily for the amusement of Nero’s court (perhaps on the occasion of the Saturnalia), at the expense of his predecessor Claudius.